Penerapan Aplikasi Scout Learning Berbasis Multimedia dalam Meningkatkan Pengembangan Inovasi Minat Dan Bakat Ekstrakurikuler Bagi Sekolah Dasar Negeri 127 Sekeloa Bandung - Sitanggang, Andri Sahata; Wahyuni, Wahyuni; Syafariani, R Fenny; Arianto, Asnandar (JURNAL PENGABDIAN KEPADA MASYARAKAT, 2019)
Creating learning innovations is one of the most important supporting factors in improving the quality of education in Indonesia and implementing it is one of the advantages that can be achieved by elementary schools in improving teaching and learning activities, with the training activities the application of multimedia-based scout applications can help teachers in make alternative learning everyday. This activity is a manifestation of the application of technology in Law Number 12 of 2012 concerning Higher Education, so that the school can develop the interests and talents of a student in primary education at the School. The innovation activities carried out included computer-based teacher training and basic student training with scout learning applications. Both of these activities are carried out by approaching teachers and students, direct dialogue about what problems are happening and implementing the best solutions by applying what application training is needed.